Reevaluasi Hak-Hak dan Pembinaan Terhadap Narapidana Narkotika dalam Sistem Pemasyarakatan di Lembaga Pemasyarakatan Narkotika Kelas II A Yogyakarta - Tahir, Ach. (UIN Sunan Kalijaga, 2016)
It is generally known that the rights of inmates have been well executed by the Wirogunan penitentiary in Yogyakarta. Some caveats need to be evaluated by the Ministry of Justice and Human Rights especially Directorate General of Corrections, there are medical service, less availability of decent food, the high cost of prison canteen food, unresponsive response to gripe, complicated remission procedure.It also needs to be considered in developing inmates that some inmates never be the member of correctional institution before, upgrading facilities, coaching personality and autonomy theinmates it self.